Manajemen Kesehatan Keluarga Pada Anggota Keluarga dengan Hipertensi dalam Tahap Perkembangan Keluarga Anak Remaja di Wilayah Depok - Astri Dwi Puspita Sari; Gusrina Komara Putri; Roland Lekatompessy (Politeknik Karya Husada, 2025)
Background: Hypertension is a chronic health problem that requires family involvement in its control and care. Families play an important role in identifying health problems, making health-related decisions, caring for sick family members, modifying the environment, and utilizing health care services. Objective: This paper aimed to describe the implementation of family nursing care for family members with hypertension. Methods: This study used a descriptive method with a case study approach involving two families with family members diagnosed with hypertension. Family nursing care was provided over one week through three home visits. Data were collected through interviews, observation, physical examination, and family assessment. Results: The assessment findings indicated family nursing problems related to hypertension health management. After three nursing visits, both families showed positive progress; however, the nursing problems were not fully resolved. The nursing diagnoses in both families were partially resolved. Conclusion: The implementation of family nursing care for family members with hypertension improved the families’ understanding and ability to care for family members with hypertension. However, the evaluation showed that the nursing problems were only partially resolved. Therefore, a longer period of family nursing assistance is needed to support more comprehensive assessment, more optimal interventions, and sustainable health behavior changes within the family.